2018
DOI: 10.1177/1541931218621332
|View full text |Cite
|
Sign up to set email alerts
|

“Sizing Up” Emerging Technology for Firefighting: Augmented Reality for Incident Assessment

Abstract: Every year, structure fires account for billions of dollars in property damage and injuries to firefighters and civilians. Emerging technologies, such as augmented and virtual reality (AR/VR) have been identified to assist in mitigating the loss of life and property, but they have not been fully evaluated. The goal of this work is to clearly identify how AR can enhance fire suppression operations by mapping feedback from a needs assessment conducted with firefighters to the areas where technology could be leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There has been limited research that studied FRs' needs for AR devices. Specifically, Kapalo et al interviewed 35 firefighters and 3 emergency management personnel to understand their challenges and identify how AR could be used to support them in the field [42]. Wilson et al interviewed 50 firefighters about their needs for head-mounted displays and revealed the drawbacks of the devices, such as blocking lower vision, stop functioning in cold weather [93].…”
Section: First Responders' Experiences With Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been limited research that studied FRs' needs for AR devices. Specifically, Kapalo et al interviewed 35 firefighters and 3 emergency management personnel to understand their challenges and identify how AR could be used to support them in the field [42]. Wilson et al interviewed 50 firefighters about their needs for head-mounted displays and revealed the drawbacks of the devices, such as blocking lower vision, stop functioning in cold weather [93].…”
Section: First Responders' Experiences With Technologiesmentioning
confidence: 99%
“…Despite the potential, AR HMDs, especially the optical seethrough HMDs, can bring new issues and risks, such as additional burden on FRs' head, limited field of view, distractions, and visibility issues of the virtual elements against the real-world background [19,26,89], which may significantly affect FRs' experiences and safety in the field. However, while mobile AR for FRs has received certain attention in the literature [1, 28,67,79,81], limited research has investigated the unique opportunities and challenges posed by head-mounted AR for FRs in the field [42,42,93], and even less work has situated FRs in an AR context to understand their first-hand experiences [24].…”
Section: Introductionmentioning
confidence: 99%
“…Brain interface and EEG instruments can help examine how various perceived information influences human individuals' analytical capabilities [92]. Some researchers examined how 2D and 3D visualization information influences firefighters' navigation decisions and field operations during emergency responses [93,94]. In the context of the SHM of bridges, this technology could help researchers analyze how various external factors influence inspectors' judgment and decision-making processes, thereby improving the reliability of inspection results.…”
Section: Human Reliability (Individual Level)mentioning
confidence: 99%
“…Consequently, there is a gap in the literature that focuses on understanding how firefighters collect and use information about response areas prior to an emergency. To address the gap in the literature related to current pre-incident practices, we employed a qualitative approach grounded in prior field studies (Kapalo et al, 2018). We also consulted two subject matter experts (SMEs) to assist in the development of the survey questions and provide feedback.…”
Section: Related Workmentioning
confidence: 99%